Josephson's clinical cardiac electrophysiology : Techniques and interpretations - Callans, David J. (Wolters Kluwer, 2021)
"The purpose of this book is to provide the budding electrophysiologist with an electrophysiologic approach to arrhythmias, which is predicated on the hypothesis that a better understanding of the mechanisms of arrhythmias will lead to more successful and rationally chosen therapy. As such, this book will stress the methodology required to define the mechanism and site of origin of arrhythmias so that safe and effective therapy can be chosen. The techniques suggested to address these issues and specific therapeutic interventions employed represent a personal view, one that is based on experience and, not infrequently, on intuition."--